Genially Interactive Media to Boost Interest in Learning Electrical Basics in Vocational Schools - Aprillia, Irma Rizky; Kurniawan, Wendy Cahya (Letters in Information Technology Education (LITE), 2024)
This development research aims to create interactive media based on Genially for the subject of “Fundamentals of Electrical Engineering.” The study aims to assess the product’s feasibility and analyze the learning interest of vocational high school (SMK) students after using this interactive learning tool. The research follows the Four-D model (Define, Design, Develop, Disseminate). The results indicate that the developed interactive learning media is highly suitable for use as a learning tool for 10th-grade vocational high school students. Based on the combined validity results of the product, a score of 92 per cent was obtained, categorizing it as highly feasible for use as a learning medium. Additionally, the implementation results showed a learning interest score of 89 per cent, categorized as very high, indicating that students have a high interest in Basic Electricity, specifically in the elements of electrical measuring instruments and testing tools, when using the Genially-based interactive learning media